Nuove modalità di organizzazione della post valutazione nella formazione online dei docenti di italiano come L1, L2 e LS - Maugeri, Giuseppe; Serragiotto, Graziano (Incontri. Rivista europea di studi italiani, 2017)
New ways of organizing feedback on evaluation in the online training of teachers of Italian as a second language or foreign language In this paper, a case study on the online training of teachers of mothertongue, second language and foreign language Italian will be examined. Specifically, this training was given to foreign language teachers of secondary school level in Italy. Critical aspects of this training have been observed referring to the assessment and evalutation carried out by tutors. This paper investigates the different links that have been created between tutors and teachers, giving solutions in order to improve assessment and evalution throught a vivid interaction between the two.